Observations of acoustic emission under conditions of varying specific film thickness for meshing spur and helical gears - Raja Hamzah, Raja Ishak (American Society of Mechanical Engineers, 2008)
This paper presents experimental findings on the generation of acoustic emission (AE) from operational spur and helical gears as a function of specific film thickness (?). The latter was varied while the gears were operating by spraying liquid nitrogen onto the rotating gear wheel over a range of load and speed conditions. It was observed that the level of AE activity was dependent on the specific film thickness (?) and consequently the level asperity contact. The presented finding on both spur and helical gears is the first known attempt at correlating friction, film thickness, and gear operating conditions with AE.